Relationship between Organizational Justice and Nurses’ Psychological Empowerment - H Zahednezhad; H Manoochehri; M Zaghari Tafreshi; P Farokhnezhad Afshar; R Ghanei Gheshlagh (نشریه پرستاری ایران, 2015)
Abstract